Stilbenes in Carex acuta and Carex lepidocarpa - Tříska, Jan; Vrchotová, Naděžda; Horník, Štěpán; Sýkora, Jan; Kučerová, Andrea (Molecules (Basel, Switzerland), 2024)
Stilbenes in the roots of Carex acuta and Carex lepidocarpa were studied. Root samples were extracted with 100% methanol and analyzed by HPLC and LC-MS. In this way, trans-resveratrol dimers (m/z 455 Da [M + H]+), trimers (m/z 681 Da [M + H]+) and tetramers (m/z 907 Da [M + H]+) were identified in the extracts. Using LC-NMR in stop-flow mode, pallidol and trans-ε-viniferin as dimers were identified. After the separation of individual peaks and their measurement by 1H NMR, cis and trans-miyabenol A as a tetramer and cis-miyabenol C as a trimer were identified. In the case of miyabenol A, it is a chromatographically inseparable mixture of cis and trans isomers in the ratio of 2:3 according to 1H NMR measurement. In the case of cis-miyabenol C, the Z-trans-trans-miyabenol C configuration was confirmed. The remaining unidentified peak with a practically identical UV-VIS spectrum to that of cis-miyabenol C is most likely another isomer of miyabenol C.
Keywords: liquid chromatography; Carex acuta; rostlinné extrakty; vysokoúčinná kapalinová chromatografie; Molecular Structure; stilbeny; Stilbenes; trans-ɛ-viniferin; NMR; Carex (rostlina); hmotnostní spektrometrie; pallidol; magnetická rezonanční spektroskopie; molekulární struktura; Chromatography, High Pressure Liquid; Plant Roots; Carex lepidocarpa; miyabenol A and C; Carex Plant; Plant Extracts; Mass Spectrometry; Magnetic Resonance Spectroscopy; kořeny rostlin